Economic performance of commercial fishing fleets off the South Brazil Shelf from Angra dos Reis (23ºS) to Rio Grande (32ºS) - Rodrigues, Amanda Ricci (2018)
In Brazil, economic data on fisheries are generally scarce, and difficult to interpret with respect to costs and fishery viability, thus making it difficult to practice consistent policy and industrial decision-making. This thesis aims to provide a cost-benefit analysis of seventeen commercial fishing fleets that operated during 2013-2014 in four port regions of the South Brazil Shelf: Angra dos Reis (AR), Santos and Guarujá (SG), Itajaí and Navegantes (IN) and Rio Grande (RG). The fleet types included the following: shrimp-trawlers, pair-bottom-trawlers, single-bottom-trawlers, bottom-gillnetters, octopus-pots, purse-seiners, surface-longliners and pole-and-line. Based on an unprecedented set of field survey data collected through interviews with vessel captains and owners, this study has the following goals: (1) to describe, calculate and compare the cost structure and gross profitability for all fleets; (2) to identify the factors (e.g., technical features and economic indicators) that determine fleet gross profit (from AR, SG and IN) using generalized additive models (GAMLSS); and (3) to assess the net profitability and viability of the fleets through the following three economic performance indicators: net profit margin (NPM), net present value (NPV) and internal rate of return (IRR). Additionally, the effects of fuel subsidy policies on profitability among South Brazil\'s fleets were evaluated. Generally, operational costs were higher than labor and fixed costs except for longliners, purse-seiners (from AR) and bottom-gillnetters (from RG), whereas labor costs were higher or had the same importance as operational costs. Fuel was the primary operational cost for all the fleets except pair-bottom-trawlers (SG) and purse-seiners (AR), for which vessel maintenance is the principal operational cost. Gross profitability varied significantly among the fleets and was clearly related to the following main factors: fuel consumption, vessel maintenance expense, ice costs, fish price and catch volume. Particularly for trawlers (from SG and IN) and all purse-seiners, technical features (i.e., vessel size and number of fishing trips, respectively) also explained profitability. Moreover, landing cost was a significant factor for those fleets\' profit. Economic performance indicators exhibited intra-fleet heterogeneity depending on region and revealed that 24% of the fleets were unviable (NPV less than zero), 23% were in fragile condition (IRRs and NPM lower than 11%), and 53% had achieved good economic returns whose IRR values exceeded 12% and whose NPM was > 10%. The worst economic performance was observed for single-bottom-trawlers (RG) and purse-seiners (SG) and the best for tuna-longliners (RG) and pair-bottom-trawlers (SG). Overall, subsidies were ineffective in increasing Rio Grande fleet profits and may be masking poor economic performance, primarily for single-bottom-trawlers (RG). Findings should guide private-sector decisions on how to protect the economic performance of the fleets, on fishery management measures (e.g., input controls, recovery plans for overfished stocks), and improve current governmental programs (e.g. the fuel subsidy program).